Enhanced anti-breast cancer efficacy of co-delivery liposomes of docetaxel and curcumin - Ye, Xi; Chen, Xin; He, Ruixi; Meng, Wangyang; Chen, Weidong; Wang, Fengling; Meng, Xiangyun (Frontiers in Pharmacology, 2022)
The successful treatment of breast cancer is hampered by toxicity to normal cells, impaired drug accumulation at the tumor site, and multidrug resistance. We designed a novel multifunctional liposome, CUR-DTX-L, to co-delivery curcumin (CUR) and the chemotherapeutic drug docetaxel (DTX) for the treatment of breast cancer in order to address MDR and the low efficacy of chemotherapy. The mean particle size, polydispersity index, zeta potential, and encapsulation efficiency of CUR-DTX-L were 208.53 ± 6.82 nm, 0.055 ± 0.001,﹣23.1 ± 2.1 mV and 98.32 ± 2.37%, respectively. In-vitro release study and CCK-8 assays showed that CUR-DTX-L have better sustained release effects and antitumor efficacy than free drugs, the antitumor efficacy was verified by MCF-7 tumor bearing mice, the CUR-DTX-L showed better antitumor efficacy than other groups, and the in-vivo pharmacokinetic study indicated that the plasma concentration-time curve, mean residence time and biological half-life time of CUR-DTX-L were significantly increased compared with free drugs, suggesting it is a promising drug delivery system for the synergistic treatment of breast cancer.